German labour costs have risen only moderately: European comparison of trends in labour and unit labour costs in 2014 and the first two quarters of 2015 - Alexander Herzog-Stein; Heike Joebges; Torsten Niechoj; Ulrike Stein; Rudolf Zwiener (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2015)
Based on Eurostat data the Macroeconomic Policy Institute (IMK) regularly analyses the development of labour costs and unit labour costs in Europe. This report presents labour cost trends in the private sector, disaggregated for private as well as public services and manufacturing industry, for a selection of European countries, the Euro Area and the European Union. In addition the development of unit labour costs in Europe is analysed, so allowing for labour productivity. Subsequently, the report examines the development of unit labor costs and the relationship between price competitiveness, export prices and unit labor costs.In 2014 hourly labour cost in the German private sector averaged 31.9 Euros. The German economy is in eighth position in the ranking of EU countries as in the previous year. With an annual rate of change of 1.8 %, the rise in labour costs in the German private sector was slightly above the European average. In the so-called European crisis countries hourly labour costs decreased again. Hourly labour costs in German manufacturing rose by 2.5 %. This is a slightly faster rate than in private services, where labour costs grew by 1.7 %. Consequently, the difference in labour costs between the two sectors diverged further and is now equal to 21 %, the largest intersectoral wage gap of all the EU countries.The adjustment process in the European crisis countries continued in 2014. Hence, the average rate of change in unit hourly labour cost in the Eurozone of 1.2 % was significantly below the ECB's inflation target of slightly below 2 % per annum. Therefore, the development of unit labour costs in the Euro Area as a whole does not comply with the ECB's inflation target. In Germany unit labour costs rose by 1.9 %. Overall, since the start of the currency union the rate of growth of unit labour costs in Germany was substantially below the ECB's inflation target. Therefore, wages in Germany should grow at an above average rate for several years to support the adjustment process in the European crisis countries. – – Das IMK analysiert regelmäßig mittels Daten von Eurostat die Entwicklung der Arbeits- und der Lohnstückkosten in Europa. In dieser aktuellen Auswertung wird die Entwicklung der Arbeitskosten in der Privatwirtschaft, im privaten und im öffentlichen Dienstleistungssektor und im Verarbeitenden Gewerbe in wichtigen europäischen Ländern sowie dem Euroraum und der Europäischen Union als Ganzes dargestellt. Im Anschluss daran wird die Entwicklung der Lohnstückkosten untersucht, dabei wird insbesondere der Frage nach dem Zusammenhang zwischen der preislichen Wettbewerbsfähigkeit, den Exportpreisen und den Lohnstückkosten nachgegangen. Im Jahr 2014 kostete in Deutschland eine Arbeitsstunde in der Privatwirtschaft 31,9 Euro. Wie im Vorjahr belegt Deutschland damit im europäischen Länderranking den achten Platz. Mit einer Veränderungsrate von 1,8 % stiegen die Arbeitskosten in Deutschland im Jahr 2014 etwas stärker als im europäischen Durchschnitt. In den Krisenländern stagnierten die Arbeitskosten oder sanken erneut. In Deutschland sind im Jahr 2014 die Arbeitskosten im Verarbeitenden Gewerbe mit 2,5 % wieder etwas stärker gestiegen als im Privaten Dienstleistungssektor. Hier waren es nur 1,7 %. Damit hat sich der Abstand zwischen beiden Wirtschaftsbereichen erneut erhöht und beträgt nun über 21 %. Das ist der größte Abstand zwischen den Sektoren von allen EU Mitgliedsländern. Die Anpassungsprozesse der Krisenländer haben sich auch im Jahr 2014 fortgesetzt, so dass die durchschnittliche Lohnstückkostenentwicklung des Euroraums mit 1,2 % deutlich unter der Zielinflationsrate der EZB von knapp 2 % lag. Damit entwickelt sich der Euroraum als Ganzes nicht stabilitätskonform. In Deutschland stiegen die Lohnstückkosten um 1,9 %. Da die deutschen Lohnstückkosten aber seit Beginn der Währungsunion deutlich schwächer gestiegen sind, als mit dem Inflationsziel der EZB vereinbar, sollten die Löhne in Deutschland über mehrere Jahre hinweg deutlich überdurchschnittlich steigen, um den Anpassungsprozess der Krisenländer zu unterstützen.
urn:nbn:de:101:1-201602178272
Keywords: 330; Arbeitskosten; Lohnstückkosten; Vergleich; Deutschland; EU-Staaten